Lecturers questioning strategies in English speaking class - Cerlya, Cerlya; Nisa, Rahmatun; Safura, Siti (ACCENTIA: Journal of English Language and Education, 2023)
The purpose of this study was to investigate the questioning strategies employed by lecturers in English speaking class. The study used a descriptive method. The participants in this study were two English lecturers who taught English Speaking skills and ten students from English Department at Universitas Muhammadiyah Aceh, Aceh Province. Data were collected by means of interview and questionnaire. The obtained data were examined by analyzing the transcription of the interview and the questionnaire responses. This study found that lecturers utilized a variety of questioning strategies, including procedural, divergent, probing, specific, and open-ended questions. Lecturers employed questioning strategies in the English classroom by asking questions at the start of the teaching and learning process and after providing the learning materials.